A Global Community of Courts? Modelling the Use of Persuasive Authority as a Complex Network - Hoadley, D.; Bartolo, M.; Chesterman, R.; Faus, A.; Hernandez, W.; Kultys, B.; Moore, A. P.; Nemsic, E.; Roche, N.; Shangguan, J.; Steer, B.; Tylinski, K.; et al. (Frontiers in Physics, 2021)
There is a growing discussion in the legal literature of an emerging global community of courts composed of a network of increasing judicial dialogue across borders. Here we investigate the use of foreign persuasive authority in common law countries by analysing the network of citations to case law in a corpus of over 1.5 million judgments given by the senior courts of twenty-six common law countries. Our corpus of judgments is derived from data available in the vLex Justis database. In this paper we aim to quantify the flow of jurisprudence across the countries in our corpus and to explore the factors that may influence a judge's selection of foreign jurisprudence. Utilisation of foreign case law varies across the countries in our data, with the courts of some countries presenting higher engagement with foreign jurisprudence than others. Our analysis shows that there has been an upward trend in the use of foreign case law over time, with a marked increase in citations across national borders from the 1990s onward, potentially indicating that increased digital access to foreign judgments has served to facilitate and promote comparative analysis. Not only has the use of foreign case law generally increased over time, the factors that may influence the selection of case law have also evolved, with judges gradually casting their research beyond the most influential and well-known foreign authorities. Notwithstanding that judgments emanating from the UK (chiefly from the courts of England and Wales) constitute the most frequently consulted body of jurisprudence, we find evidence that domestic courts favour citing the case law of countries that are geographically proximal.